Characteristics of Fundus Autofluorescence Imaging at 795 nm and its Correlations with Postoperative Outcomes for Idiopathic Macular Hole - Zhang, Ximei; Yue, Huifang; Liu, Chenyu; Shi, Yuexin; Zhang, Yunda (Current Medical Imaging, 2024)
Background:Vitrectomy combined with internal limiting membrane (ILM) peeling or ILM inverted flap greatly improves hole closure and vision prognosis for idiopathic macular holes (IMH). The application of indocyanine green (ICG) in MH surgery increases the visibility of ILM and the safety of surgery. However, the area of ILM peeling and the state of the flap and a closed hole has not been well observed.Aims:Fundus autofluorescence at 7935nm can show the range of ILM peeling and the state of the hole site and ILM flap by monitoring residual ICG postoperatively. However, the characteristics of fundus autofluorescence especially the site of the closed hole, and its relationship with vision prognosis have not been explored. The aim of this project was to find the autofluorescence features of the closed hole and their relation with vision.Objectives:To investigate the characteristics of fundus autofluorescence imaging after ICG-assisted vitrectomy for IMH and to evaluate the correlations of fluorescence patterns at the MH site with visual acuity and macular anatomic outcomes.Methods:We retrospectively evaluated 33 IMH patients (33 eyes) who underwent a 25G pars plana vitrectomy (follow-up, 6-14.5 months). ICG staining (2.5 mg/mL) was either used to remove the internal limiting membrane (ILM) or the inverted ILM flap was overlaid on the hole. After surgery, fluorescence imaging of the fundus was obtained using a scanning laser ophthalmoscope at 795 nm.Results:On fluorescence imaging, the area of ILM peeling in all eyes showed hypofluorescence with no changes over time. The inverted ILM flap (performed in 18 eyes) was positioned on the inferior retina and exhibited early mild hyperfluorescence with blurred edges. This was gradually enhanced up to 3-6 months postoperatively and was then attenuated. MHs showed two distinct patterns on optical coherence tomography: granular (21 eyes) and patchy hyperfluorescence (12 eyes). Best-corrected visual acuity improved postoperatively in all cases (p<0.001, Z=-4.744). VA was worse in the patchy (vs. granular) hyperfluorescence cases (p=0.011, Z=-2.548).Conclusion:The status of the ILM peeling area, ILM flap, and closed MH can be clearly observed using autofluorescence imaging at 795 nm. Fluorescence may be due to ICG staining of the ILM and accumulation in retinal pigment epithelium cells during ICG-assisted surgery. Granular hyperfluorescence at the MH site may indicate good anatomic and visual prognoses.
Keywords: Postoperative outcomes